2016
DOI: 10.1007/s11120-016-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies on structural changes and oligomerisation of violaxanthin de-epoxidase associated with the pH-dependent activation

Abstract: Violaxanthin de-epoxidase (VDE) is a conditionally soluble enzyme located in the thylakoid lumen and catalyses the conversion of violaxanthin to antheraxanthin and zeaxanthin, which are located in the thylakoid membrane. These reactions occur when the plant or algae are exposed to saturating light and the zeaxanthin formed is involved in the process of non-photochemical quenching that protects the photosynthetic machinery during stress. Oversaturation by light results in a reduction of the pH inside the thylak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Carotenoid biosynthetic enzymes appear to be either associated to envelope and thylakoid membranes (PSY, PDS, ZDS, CRTISO, LCYB, LCYE, CYP97A and CYP97C) or integral membrane proteins (ZISO, BCH) [43,63]. VDE attaches to the thylakoid membrane at acidic pH but behaves as a soluble lumenal protein at neutral pH [89]. PSY has also been found in plastoglobules or the stroma of chloroplasts from different species [64,90], while in the plastids of dark-germinated seedlings (i.e.…”
Section: Enzyme Distribution Within Plastidsmentioning
confidence: 99%
“…Carotenoid biosynthetic enzymes appear to be either associated to envelope and thylakoid membranes (PSY, PDS, ZDS, CRTISO, LCYB, LCYE, CYP97A and CYP97C) or integral membrane proteins (ZISO, BCH) [43,63]. VDE attaches to the thylakoid membrane at acidic pH but behaves as a soluble lumenal protein at neutral pH [89]. PSY has also been found in plastoglobules or the stroma of chloroplasts from different species [64,90], while in the plastids of dark-germinated seedlings (i.e.…”
Section: Enzyme Distribution Within Plastidsmentioning
confidence: 99%
“…Activation of VDE is probably driven by a dimerization of the water-soluble monomeric VDE, followed by the binding of the active, dimeric VDE to the lumen side of the thylakoid membrane (Hager and Holocher, 1994;Arnoux et al, 2009;Saga et al, 2010). With regard to the dimerization it has been proposed that the C-terminus of the VDE plays a role in the interaction of the VDE monomers (Hallin et al, 2016) and that four specific amino acid residues are important for the pH-dependent activation (Fufezan et al, 2012). In addition, it has been suggested that the conserved cysteine residues and the disulfide bridges formed by the cysteines are sensitive to redox changes of the thylakoid membrane induced by the photosynthetic electron transport (Hallin et al, 2015;Simionato et al, 2015).…”
Section: Reaction Sequences and Xanthophyll Cycle Enzymesmentioning
confidence: 99%
“…VDE is the first described putative plant lipocalin (Bugos and Yamamoto 1996) and has been classified as a lipocalinlike protein (Charron et al 2005). The activation of VDE is related to the conformational change (Kawano and Kuwabara 2000) and the formation of an ɑ-helical coiled structure located at the C-terminal domain (Hallin et al 2016). Other research has reported that VDE uses ascorbic acid as a secondary substrate, possibly as a monomer.…”
Section: Introductionmentioning
confidence: 99%